Synthesis And Charcterization Of Diblock Copolymers Containaing Monothio-orthoester Functions Using Raft Polymerization - Hadjout, S.; Haraoubia, R.; Benabdelghani, Z. (University of Eloued جامعة الوادي, 2017)
The acyclic and cyclic monothio-orthoester monomers were synthesized by modification of aromatic monomers containing dithioester function in the side chain. Reversible addition-fragmentation chain transfer (RAFT) polymerization was employed for the preparation of polymers containing a dithioester end as macro-chain transfer agents (macro-CTA) using 4-benzyl methyldithiobenzoate (BMDTB) as chain transfer agent (CTA) and 2,2-azobisisobutyronitrile (AIBN) as initiator. A series of diblock copolymers were prepared by RAFT copolymerization of MVDTB, MMMS and MVPOCO, using the different macro-chain transfer agents (macro-CTA) and AIBN as initiator. All polymerizations were carried out at 60 °C for 24 or 30 hours in dry THF. Homopolymers and diblock copolymers are characterized by 1H NMR, 13C NMR, IR, SEC, DSC and TGA.
Article in Journal of Fundamental and Applied Sciences Vol 09, N 01
Keywords: Dithioesters, monothio-orthoesters, RAFT polymerization.